Surface Modification and Dyeing of Ultra-High Molecular Weight Polyethylene Fibers by Plasma Discharge Mode - A. Elabid, Amel. E.; Hassan, Elwathig. A. M.; Jing, ZHANG (Gezira Journal of Engineering and Applied Sciences, 2019)
In this study Ultra-high molecular weight polyethylene (UHMWPE) fibers were subjected to oxygen/argon plasma treatment in order to improve the wettability without changing bulk properties. The results showed that surface roughnesshave been modified by plasma treatment, indicating that the plasma treatment favored the interaction with dyeing UHMWPE fibers. After the treatment the treated fibers were characterized by using scanning electron microscopy (SEM),Fourier transforms infrared spectroscopy analysis (FT-IR), X-ray Diffraction (XRD), atomic force microscopy (AFM). Dyeability of the modified fibers were investigated by dyeing using disperse blue dye and also fibers were printed with pigment red colour.The obtained results were compared with the dyeability of the untreated fiber. The result showed that a significant increase of K/S value after dyeingandafter printing at dyeing temperature of 100 ° C. Thus, the oxygen/argon plasma treatment of UHMWPE fiber can obtain good dyeing properties overall, plasma treatment has a great improvementof theroughnesssurface and dyeing property of UHMWPE fiber.        تعرضت ألياف البولي إيثيلين عالية الوزن الجزيئي  للعلاج بتحفيز البلازما باستخدام خليط من الارجون والاكسجين من أجل تحسين قابلية الامتصاص دون تغيير خصائص الالياف. أظهرت النتائج أن خشونة السطح قد تم تحسينها عن طريق معالجة البلازما، مما يشير إلى أن معالجة البلازما تحسن التفاعل مع صباغة ألياف البولي إيثيلين عالية الوزن الجزيئي. اختبرت الألياف المعالجة عن طريق جهاز مجهر المسح الإلكتروني (SEM)، حيث يقوم فوراً بالتحليل الطيفي بالأشعة تحت الحمراء (FTIR)، انحراف الأشعة السينية (XRD)، الفحص بمجهر القوى الذرى (AFM). تم فحص صباغة الألياف المعدلة عن طريق الصباغة باستخدام الصبغة الناشرة الزرقاء وطباعة الياف أخرى بالوان البجمنت الحمراء. تمت مقارنة النتائج التي تم الحصول عليها بعد الصباغة مع الألياف غير المعالجة. أظهرت النتيجة ان هنالك زيادة كبيرة في قيمة K / S بعد الصباغة والطباعة عند الصباغة في درجة حرارة 100 درجة مئوية. وبالتالي، فإن معالجة ألياف البولي إيثيلين عالية الوزن الجزيئي  بتحفيز البلازما باستخدام خليط من الارجون والاكسجين يمكن أن تحصل على خصائص صباغة جيدة بشكل عام، والمعالجة بتحفيز البلازما يعمل على تحسن كبير في خشونة السطح وخاصية الصباغة لالياف البولي إيثيلين عالية الوزن الجزيئي.